2019
DOI: 10.1016/j.tjem.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic colitis due to antiphospholipid antibody syndrome

Abstract: IntroductionPortal system ischemia may present insidiously which may aggravates the prognosis.Case presentationA 26-year old man presented with watery diarrhea and generalized abdominal pain for 3 months. On physical examination, moderate splenomegaly was noticeable. Stool exam and culture was negative except for blood in stool. Colonoscopy was in favor of inflammatory bowel disease although the patient symptoms have worsened despite treatment. Abdominopelvic computed tomography (CT) showed thromboses in porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our patient is the first pediatric-onset (onset age at the 8) lupus case complicated by stercoral colitis without a disease flare or NSAID medication use. Although there is a reports that ischemia colitis is associated with antiphospholipid syndrome ( 24 ), but reviewing her 20-year history of lupus, no antiphospholipid antibodies were found. In addition, it is reported that some anticonvulsants can induce stercoral colitis ( 25 ), but only one short-term benzodiazepines was used 9 year ago to control a seizure.…”
Section: Discussionmentioning
confidence: 88%
“…Our patient is the first pediatric-onset (onset age at the 8) lupus case complicated by stercoral colitis without a disease flare or NSAID medication use. Although there is a reports that ischemia colitis is associated with antiphospholipid syndrome ( 24 ), but reviewing her 20-year history of lupus, no antiphospholipid antibodies were found. In addition, it is reported that some anticonvulsants can induce stercoral colitis ( 25 ), but only one short-term benzodiazepines was used 9 year ago to control a seizure.…”
Section: Discussionmentioning
confidence: 88%